Association between effective hepatic blood flow and the severity and prognosis of hepatitis B virus-related acute on chronic liver failure. Issue 2 (February 2021) - Chen, Dabiao; Wen, Shihua; Wu, Zebin; Gu, Yurong; Chen, Youming; Chen, Xiaotong; Zhang, Yanyan; Lin, Binliang; Peng, Liang; Zheng, Yubao; Gao, Zhiliang
Abstract : Background: Hepatic inflammation resulted in hepatocyte necrosis and microcirculatory dysfunction in acute on chronic liver failure (ACLF) with cirrhosis or not. The influence of effective hepatic blood flow (EHBF) on the severity of liver failure has not been fully elucidated. Aim: The aim of this study was to assess the correlation between the EHBF and the severity and the prediction of 90-day mortality rate of hepatitis B virus-related ACLF (HBV-ACLF). Methods: In this retrospective study, patients hospitalized for HBV-ACLF or decompensated cirrhosis and who underwent an indocyanine green (ICG) clearance test between June 2016 and July 2018 were enrolled. EHBF was measured by the ICG clearance test and patients were categorized into the ACLF without cirrhosis (HBV-ACLF-no-Cir), ACLF with cirrhosis (HBV-ACLF-Cir) and decompensated cirrhosis (HBV-De-Cir). Results: A total of 522 patients (HBV-ACLF-no-Cir: 84, HBV-ACLF-Cir: 111 and HBV-De-Cir: 327) were enrolled. The mean EHBF in the HBV-De-Cir was significantly higher than that in the HBV-ACLF-no-Cir and HBV-ACLF-Cir (0.36 vs. 0.21 vs. 0.20 L/min, P  < 0.001). EHBF was significantly correlated with the total bilirubin, prothrombin activity and model for end-stage liver disease (MELD) in the HBV-ACLF-no-Cir. The predicted 90-day mortality rate using the MELD, EHBF, ICG-retention rate at 15 min (R15%) and EHBF-R15% scores were similar. The sensitivity and specificity of the EHBF varied between 68.5–80.2% and 45.8–73.7%, respectively. The EHBF-MELD score had the highest specificity. Conclusion: EHBF was significantly lower in the patients with ACLF compared to decompensated cirrhosis. The EHBF were closely related to the severity of HBV-ACLF and can be used for predicting the 90-day mortality rate of HBV-ACLF. Abstract : Supplemental Digital Content is available in the text.